Text mining Nahdawi discourses: topic modeling Taha Hussein’s reformist legacy - Talaat F Mohamed (22928851) (2025)
This study re-examines the intellectual, cultural, and literary legacy of Taha Hussein (1889–1973), a pivotal reformist thinker of the Arab Nahda (renaissance or awakening). Integrating computational methods from the digital humanities, specifically topic modeling applied to a 42-work corpus, with traditional close textual analysis, the study uncovers the structural and thematic patterns underpinning Hussein’s discourse on identity, modernization, and cultural reform. The analysis foregrounds on his syncretic humanism, which weaves together Egypt’s Pharaonic, Arab-Islamic, Mediterranean, and European inheritances into a pluralistic national vision. It highlights his critique of essentialist binaries, his advocacy for educational democratization, and his integrative approach to mediation, translation, and nation-building. Situated within the (post)colonial frameworks, the study critically engages debates around Hussein’s perceived Occidentalism while affirming his enduring relevance to contemporary discourses on intellectual sovereignty, cultural revival, and the humanistic foundations of reform. This research contributes to digital humanities by demonstrating the value of topic modeling for mapping the complex intellectual landscape of a major non-Western historical figure across a large corpus. It offers a scalable methodology for revealing latent thematic structures that complement traditional hermeneutic approaches in Arabic and Middle Eastern studies. By bridging digital methodologies with close reading, this study reframes Hussein’s reformism as a dynamic transcultural project that resists reductive polemics and illuminates postcolonial identity formation and the global positioning of Arab thought. Other Information Published in: Digital Scholarship in the Humanities License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/llc/fqaf085